Pengaruh Budaya Organisasi dan Lingkungan Kerja Fisik terhadap Kinerja Karyawan pada Sapphire Sky Hotel BSD Kota Tangerang Selatan - Muhamad Rifqi; Irwansyah Irwansyah (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2025)
This research aims to analyze the influence of organizational culture and physical work environment on employee performance at Sapphire Sky Hotel BSD South Tangerang City. The background of this research is the importance of the role of a strong organizational culture and a comfortable physical work environment in supporting the creation of optimal employee performance. This research uses a quantitative method with an associative approach because it aims to determine the relationship and influence between independent variables and dependent variables. The research sample consisted of 64 respondents which was determined through a saturated sampling technique, namely the entire population was used as a respondent. Data processing is carried out with the help of the SPSS program version 25 through the stages of validity test, reliability, classical assumption test, multiple linear regression analysis, correlation coefficient, coefficient of determination, and hypothesis testing using t test and F test. The research results show that partially organizational culture (X1) has a positive and significant effect on employee performance (Y). This is proven by the calculated t value of 3.236 greater than the t table of 1,999, and the significance value of 0.002 which is less than 0.05. Furthermore, the physical work environment (X2) also has a positive and significant influence on employee performance with a calculated t value of 4,441 greater than the table t of 1,999 and a significance value of 0.000 < 0.05. Simultaneously, both free variables have a positive and significant influence on employee performance, shown by the results of the F test with a calculated F value greater than the F table and a significance of 0.000 < 0.05. The determination coefficient value of 65.6% indicates that employee performance is influenced by organizational culture and physical work environment, while the remaining 34.4% is influenced by other factors outside this study.